(3BdjGJ MeGjI Mbhb GdEfSGf Hjf GdfXQjI hGdJWHjbGJ (B/s - (3ZRGd, YKeGfs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2021)
(3Gdhbha Ydi JaGUjd BdjGJ MeGjI Mbhb GdEfSGf HGdfSHI dYed GdSdWI GdJfajPjI SJchf NWI GdHMK aj gPG GdehVhY ceG jdj (B: (3GdEgOGA, ebOeI, aUd JegjOj (B: (3eGgjI Mbhb GdEfSGf aj GdTQjYI GdESdGejI hGdbhGfjf GdhVYjI, GdeHMK GdChd (B: (3eGgjI Mbhb GdEfSGf aj GdTQjYI GdESdGejI, GdeHMK GdKGfj (B: (3eGgjI Mbhb GdEfSGf aj GdbhGfjf GdhVYjI, GdHGH GdChd (B: (3GdLhGfH GdCefjI dMeGjI Mbhb GdEfSGf, GdaUd GdChd (B: (3GdSdWGJ GdJfajPjI hMbhb GdEfSGf Hjf GdEWdGb hGdJbjjO, GdeHMK GdChd (B: (3OhQ GdSdWI GdJfajPjI aj MeGjI Mbhb GdEfSGf, GdeHMK GdKGfj (B: (3GdeHGOF GdJj JMce Yed GdSdWI GdJfajPjI aj eLGd Mbhb GdEfSGf, GdaUd GdKGfj (B: (3GdCLgRI GdCefjI hMbhb GdEfSGf, GdeHMK GdChd (B: (3efXeI GdYah GdOhdjI heHGOF GSJNOGe CSdMI GdbhI hGdCSdMI GdfGQjI, GdeHMK GdKGfj (B: (3GdLeYjI GdYGeI ddCee GdeJMOI, GdHGH GdKGfj (B: (3GdLhGfH GdCNdGbjI dMeGjI Mbhb GdEfSGf, GdaUd GdChd (B: (3GdLhGfH GdfXQjI dMbhb GdEfSGf, GdaUd GdKGfj (B: (3GdLhGfH GdJWHjbjI dMbhb GdEfSGf(B.s
(3HHdjhLQGajI (B: (3UaMI (B417-445.s
Keywords: (3Mbhb GdEfSGf (B((3abg ESdGej(B)s; (3Mbhb GdEfSGfs -- (3bhGfjf hJTQjYGJs -- (3eUQs